2015
DOI: 10.1093/jac/dku523
|View full text |Cite
|
Sign up to set email alerts
|

Silver resistance in Gram-negative bacteria: a dissection of endogenous and exogenous mechanisms

Abstract: ObjectivesTo gain a more detailed understanding of endogenous (mutational) and exogenous (horizontally acquired) resistance to silver in Gram-negative pathogens, with an emphasis on clarifying the genetic bases for resistance.MethodsA suite of microbiological and molecular genetic techniques was employed to select and characterize endogenous and exogenous silver resistance in several Gram-negative species.ResultsIn Escherichia coli, endogenous resistance arose after 6 days of exposure to silver, a consequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
255
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(276 citation statements)
references
References 44 publications
18
255
1
2
Order By: Relevance
“…In contrast, the Gram-negative Enterobacter cloacae strain (ATCC 13047) with a genomically encoded silver resistance cassette became resistant after 5 cycles, whereas another randomly chosen Enterobacter cloacae strain (ATCC 23355) did not acquire resistance. It has recently been shown in Gram-negative bacteria that silver resistance requires an efflux transport system and either a loss of outer membrane porin or an additional periplasmatic silver sequestration protein (26). Our study strengthens the fact that this concerted action against intracellular silver is so far neither known to be inherent nor inducible for Gram-positive bacteria, which makes silver coatings interesting for clinical use.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, the Gram-negative Enterobacter cloacae strain (ATCC 13047) with a genomically encoded silver resistance cassette became resistant after 5 cycles, whereas another randomly chosen Enterobacter cloacae strain (ATCC 23355) did not acquire resistance. It has recently been shown in Gram-negative bacteria that silver resistance requires an efflux transport system and either a loss of outer membrane porin or an additional periplasmatic silver sequestration protein (26). Our study strengthens the fact that this concerted action against intracellular silver is so far neither known to be inherent nor inducible for Gram-positive bacteria, which makes silver coatings interesting for clinical use.…”
Section: Discussionsupporting
confidence: 81%
“…Despite this broad clinical use, little is known about the stability of silvercoated alloys, their efficacy on biofilm-forming bacteria-especially in combination with antibiotics-and the kinetics of release. Moreover, silver has a broad range of bacterial targets, including the respiratory chain (21)(22)(23)(24), and has been shown to induce resistance in Gram-negative bacteria and toxicity in eukaryotic cells (25,26).…”
mentioning
confidence: 99%
“…Rather, resistance to silver is a by-product of copper resistance and cadmium is a by-product of zinc resistance. In fact, resistance studies with S. aureus were unable to produce silver-resistant strains even after 42 days of continuous passage in the presence of AgNO 3 (Randall et al 2013) Similar results were observed for some Gram-negative organisms, whereas in E. coli strains, silver resistance arises as a result of mutations in both ompR and cusS or mediated through the sil system (Randall et al 2015).…”
Section: Copper and Zinc Resistance In Gram-positive Bacteriamentioning
confidence: 52%
“…One, the pco determinant was first isolated from plasmid pRJ1004 from an Australian pig E. coli isolate (Brown et al 1995) and confers copper resistance. The other, the sil determinant originally located on Salmonella Typhimurium plasmid pMG101, but later shown to have transferred into the chromosome of the host E. coli K-12 J53 strain (Randall et al 2015), is associated with silver resistance (McHugh et al 1975;Gupta et al 1999). Later sequencing of pRJ1004 (NCBI accession no.…”
Section: Introductionmentioning
confidence: 99%
“…Like the Sil system, the cus operon includes genes for a sensor kinase (Sil/CusS), a periplasmic efflux transporter (Sil/CusBCA), and a periplasmic Ag ϩ binding protein (Sil/ CusF). The two systems share Ͼ80% amino acid identity, and both are thought to function primarily via silver efflux (24,25).…”
mentioning
confidence: 99%